2020
DOI: 10.4103/jiaps.jiaps_233_18
|View full text |Cite
|
Sign up to set email alerts
|

Our Laparoscopic Surgical technique and experience in treating pediatric inguinal hernia over the past decade

Abstract: Background:Over the past decade, laparoscopic hernia repair was the most performed operation in our department. Equally, it compromises 15% of all pediatric operations performed. We aim, in this study, to review all the cases performed and extrapolate important information like reoccurrences, the incidence of metachronous inguinal hernia, complications amongst other information.Material and Methods:All patients under the age of 18 whom underwent elective laparoscopic hernia repair between 03/01/2007 till the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
2
7
3
1
Order By: Relevance
“…Additionally, the ratio of unilateral: bilateral and right: left: bilateral was 6.9:1 and 4.1:2.8:1 respectively, equal to other studies [9].…”
Section: Discussionsupporting
confidence: 68%
“…Additionally, the ratio of unilateral: bilateral and right: left: bilateral was 6.9:1 and 4.1:2.8:1 respectively, equal to other studies [9].…”
Section: Discussionsupporting
confidence: 68%
“…From the results, we concluded that the ratio of male to female inguinal hernia was 4.8:1, which was higher than the reported 2.5:1 [9]. Our study boasts of participant volume almost 10-12 times more than the reported articles [9] and we postulate that our result may be a better representation of the true morbidity. Additionally, the ratio of unilateral: bilateral and right: left: bilateral was 6.9:1 and 4.1:2.8:1 respectively, equal to other studies [9].…”
Section: Discussioncontrasting
confidence: 47%
“…Based on the results, we concluded that the ratio of male to female inguinal hernia was 4.8:1, which was higher than the reported 2.5:1 [9]. Our study boasts of participant volume almost 10-12 times more than the reported articles [9] and we postulate that our result may be a better representation of the true morbidity.…”
Section: Discussioncontrasting
confidence: 41%
“…Inguinal hernia is a common disease in pediatric patients with an estimated incidence of 1-5% [1] and hernia repair compromises of up to 15% of all operations in some pediatric centers [9]. Since the 1960s, Beijing Children's Hospital has implemented several measures to meet the increasing demands of inguinal hernia patients in the outpatient department [10], which we attribute to heightened awareness of the disease in parents (Figure 1).…”
Section: Discussionmentioning
confidence: 99%